2021
DOI: 10.3389/fphys.2021.634838
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Allelic Variants Associated With Cold Tolerance of PmPIAS in Pinctada fucata martensii

Abstract: The protein inhibitor of activated STAT (PIAS) functions in diverse aspects, including immune response, cell apoptosis, cell differentiation, and proliferation. In the present study, the PIAS in the pearl oyster Pinctada fucata martensii was characterized. The sequence features of PmPIAS were similar to that of other PIAS sequences with PIAS typical domains, including SAP, Pro-Ile-Asn-Ile-Thr (PINIT), RLD domain, AD, and S/T-rich region. Homologous analysis showed that PmPIAS protein sequence showed the conser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In the present study, 18 SNPs from PmMYH were found to be strongly associated Note: Mean values with the same letter within a column are not significant different (p > 0.05). Lai et al, 2021). Of these associated SNPs, two cross-tested in the golden selection line and base stock, further indicating its potential in growth trait construction.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In the present study, 18 SNPs from PmMYH were found to be strongly associated Note: Mean values with the same letter within a column are not significant different (p > 0.05). Lai et al, 2021). Of these associated SNPs, two cross-tested in the golden selection line and base stock, further indicating its potential in growth trait construction.…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, 18 SNPs from PmMYH were found to be strongly associated with growth traits, indicating its potential in growth selection. Several SNPs such as SNP 31, 57, 85 and 89 lack one of the three possible genotypes, which indicated that these SNP genotypes disappearance were the consequence of local adaptation or selection (Du et al, 2014; Lai et al, 2021). Of these associated SNPs, two cross‐tested in the golden selection line and base stock, further indicating its potential in growth trait construction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative real-time RT-PCR (qRT-PCR) was performed with b-actin as the reference gene to determine mRNA expression. Research has showed that b-actin was the most stable reference gene for different tissues and different embryonic developmental stages (Wang and He, 2013) and have been widely used as reference genes for qRT-PCR analysis (Wang et al, 2019;Lai et al, 2021;Chen et al, 2022). qRT-PCR was performed with SYBR Green Master Mix (Thermo-Fisher Scientific, USA) according to the protocol recommended by the manufacturer.…”
Section: Analysis Of Pm5-htr2 and Pm5-htr4 Expressionmentioning
confidence: 99%